The Effect of Financial Performance On The Price Earning Ratio (PER) And Its Implications For Stock Prices (Study On Companies Listed On The Idx In 2018–2021) - Aris Munandar; Harsi Romli; Havis Aravik; Edward Tember Saut Halomoan Simatupang (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2024)
This research was conducted on 486 issuers that have gone public on the Indonesian Stock Exchange (BEI). This research aims to determine the influence of financial performance on the Price Earnings Ratio (PER) and its implications for stock prices in the period 2018–2021. The analysis technique uses panel data regression, and data processing uses the EViews application. The results of the research illustrate that the NPM variable has a significant positive effect on PER; if NPM increases by 1%, it will be able to increase PER by 0.055 times, while the ROA and DAR variables have an insignificant negative effect on PER; if ROA increases by 1%, it will be able to reduce PER by 0.020 times, and the same applies to DAR; if DAR increases by 1%, it can reduce PER by 0.0090 times. Independent variables (ROA, NPM, and DAR) simultaneously influence PER. Based on the adjusted R-squared, the three independent variables affect a PER of 81.70%. The PER variable has a significant positive effect on share prices. If PER increases by 1 time, it will increase the share price by IDR. 0.000722. Based on adjusted R-squared, PER has an effect of 99.9% on share prices.